Spiritual Leadership and Lecturer Performance in Indonesian Private Higher Education: Unveiling the Sequential Mediating Roles of Job Satisfaction and Organizational Commitment - Ilham; St. Sukmawati; Ramlawati; Andi Tenri Olle; Murad Lahadji (Global Research Collaboration, 2026)
This study investigates the direct and indirect effects of spiritual leadership on lecturer performance through the sequential mediating roles of job satisfaction and organizational commitment. A quantitative explanatory research design was employed using a cross-sectional survey of 312 lecturers from private universities in Southeast Sulawesi, Indonesia. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results reveal that spiritual leadership significantly enhances lecturer performance both directly and indirectly. Spiritual leadership positively affects job satisfaction and organizational commitment, while both variables significantly contribute to lecturer performance. Furthermore, job satisfaction positively influences organizational commitment. Mediation analysis confirms that job satisfaction and organizational commitment function not only as independent mediators but also as sequential mediators linking spiritual leadership and lecturer performance. The structural model explains 68.7% of the variance in lecturer performance, indicating substantial explanatory power. This study extends spiritual leadership theory by integrating social exchange theory and attitude theory to explain the psychological mechanisms through which leadership influences lecturer performance. The findings highlight the importance of fostering vision, hope/faith, and altruistic love to strengthen lecturers’ job satisfaction, organizational commitment, and performance in teaching, research, and community service activities within higher education institutions.